Partnership Schemes - A Solution to Sustain Raw Materials of Plywoods in Lombok Island - SUSILOWATI, Etty; AKBAR, R. Maulana Aliif (Journal of Environmental Management and Tourism; Vol 9 No 2 (2018): JEMT Volume IX Issue 2(26) Spring 2018, 2018)
The increasing number of community plantation forests in Indonesia, specializing in plywood, has improved the size of this market. Many companies succeed in this business, creating fierce competition for raw material supplies. Additionally, the Indonesian government has intensified the wood industry production in 2015 so that several fast growing and shortage timber species were introduced. However, this great opportunity is also faced with the challenge that timber exported overseas must be certified. The existence of middlemen in the business supply chain can potentially disrupt the business with unsustainable procedures and can harm the environment. In this study, we investigated the requirements of a partnership to establish a sustainable partnership with the local communities, to provide a sustainable environmental development in Lombok and to deliver profitable business prospects to the wood industries. This research focused on investigating Dharma Satya Nusantara Group (DSNG)’s challenge to obtain and to secure raw materials of wood to maintain and to sustain its future plywood manufacturing businesses. A qualitative method was employed by using snowball sampling of 17 individuals, including farmers, landowners, NGOs, middlemen, and logistic companies. Finally, a triangulation method was employed to analyze the data. Our findings proved that a mediator was needed to find mutual goals between private sectors in the local community. The mediator position should be neutral and prohibit from taking a side. DSNG as the buyer could utilize an expert practitioner that would act as a mediator to connect with the people, while the farmers would be supported by cooperation as their connector to DSNG. Finally, a collectivist culture, mutual trust, solidarity, teamwork, and education were essential factors for sustainable partnership.